FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP VOLUNTARY AUDITOR SWITCHING (Kajian pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Periode Tahun 2018-2020) - Rahayu Sulistiyani; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2022)
The change of auditor is a mandatory way to overcome the problem of auditor independence in Indonesia. Auditor switching may occur because of the government regulations (mandatory) or the will of the company (voluntary). When the company conducts a voluntary auditor switching, it will raise various questions because this happens outside of the regulations set by the government. This research aims to analyze and find empirical evidence of the factors affecting voluntary auditor switching. These factors are CPA firm size, audit opinion, management change, financial distress, and managerial ownership. The population in this research was a manufacturing sector company listed on Indonesia Stock Exchange (IDX) from 2018 to 2020. The data collection technique used is purposive sampling with a total sample of 47 manufacturing companies and an observation period of 3 years, so the total observations of 141 data were obtained. We used the logistic regression analysis method using SPSS 26. The results showed that the variable of CPA firm size has a significant effect on voluntary auditor switching. Meanwhile, other variables in this research like audit opinion, management changes, financial distress, and managerial ownership have no significant effect on voluntary auditor switching.